HUBUNGAN ASUPAN KALIUM, PERSENTASE LEMAK TUBUH, DAN KEPATUHAN DIET RENDAH GARAM DENGAN KEJADIAN HIPERTENSI TERKONTROL DAN TIDAK TERKONTROL PADA PRALANSIA DI RW 03 LUBANG BUAYA DAN RW 09 KAMPUNG TENGAH, JAKARTA TAHUN 2020 - Amelia Eka Putri (2020)
Hypertension is still a health problem that causes death worldwide. In 2018, Indonesia has a prevalence of hypertension based on age over 18 years of 34.1%. Uncontrolled hypertension is someone who has hypertension with a condition of blood pressure greater than or equal to 140 mmHg / 90 mmHg and does not do regular checks. This study aims to determine the relationship between potassium intake, body fat percentage and low salt diet adherence with the incidence of controlled and uncontrolled hypertension in pre-elderly at RW 03 Lubang Buaya and RW 09 Kampung Tengah, Jakarta 2020. This study used a cross sectional design. The total sample of 81 respondents taken by simple random sampling technique. The research instrument used a semi quantitative food frequency questionnaire form, Bioelectrical impedance analysis and a low salt diet compliance questionnaire. The results of the analysis using the chi square test obtained potassium intake (p = 0.182), body fat percentage (p = 0.984), low salt diet compliance (p = 0.000). There is a relationship between low-salt diet adherence with the incidence of controlled and uncontrolled hypertension in pre-elderly. Meanwhile, potassium intake and body fat percentage did not show any relationship with the incidence of controlled and uncontrolled hypertension in pre-elderly. Thus, it is hoped that cadres in Posbindu will be active in providing education related to hypertension and the importance of maintaining blood pressure in order to remain under control.